1986
DOI: 10.1095/biolreprod35.3.725
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Macroscopic Appearance of the Surface of Bovine Ovarian Follicles, Concentrations of Steroids in Follicular Fluid, and Maturation of Oocytes in Vitro1

Abstract: The relationship among opaqueness of the surface of bovine ovarian follicles, concentrations of follicular steroids, and capacity of oocytes to achieve nuclear maturation in vitro was examined in this study. Follicles greater than or equal to 5 mm in diameter were classified as clear (n=68) or opaque (n=72) based on their surface appearance. An oocyte and follicular fluid (FF) were removed from each follicle. Each oocyte was cultured, and the concentration of estradiol (E), progesterone (P), and testosterone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 0 publications
2
15
0
2
Order By: Relevance
“…The results reported here are in accordance with those of previous studies showing different oestradiol concentration of atretic and intact follicles in cattle and horses (Grimes and Ireland, 1986;Guilbault et al, 1993;Goudet et al, 1999;Ginther et al, 2002), although they did not indicate differences between nonatretic and early atretic follicles. In contrast to some previous studies, the highest progesterone concentrations were found in follicles with the quickest increase of diameter (McNatty et al, 1984;Grimes and Ireland, 1986;Guilbault et al, 1993). However, in conformity with the findings of these authors the progesterone concentrations of the follicular fluid were higher in regressing follicles than in small growing follicles.…”
Section: Discussionsupporting
confidence: 93%
“…The results reported here are in accordance with those of previous studies showing different oestradiol concentration of atretic and intact follicles in cattle and horses (Grimes and Ireland, 1986;Guilbault et al, 1993;Goudet et al, 1999;Ginther et al, 2002), although they did not indicate differences between nonatretic and early atretic follicles. In contrast to some previous studies, the highest progesterone concentrations were found in follicles with the quickest increase of diameter (McNatty et al, 1984;Grimes and Ireland, 1986;Guilbault et al, 1993). However, in conformity with the findings of these authors the progesterone concentrations of the follicular fluid were higher in regressing follicles than in small growing follicles.…”
Section: Discussionsupporting
confidence: 93%
“…However, structural changes associated with oocyte maturation are associated with changes in steroid concentrations. Concentrations of P 4 and E 2 that develop in the preovulatory follicle may be involved in oocyte maturation in cattle [23]. Elevated intrafollicular concentrations of E 2 were postulated to prevent premature nuclear maturation of bovine oocytes in vivo [23].…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of P 4 and E 2 that develop in the preovulatory follicle may be involved in oocyte maturation in cattle [23]. Elevated intrafollicular concentrations of E 2 were postulated to prevent premature nuclear maturation of bovine oocytes in vivo [23]. When oocytes were examined within a few hours of removal from a follicle, less than 10% of bovine oocytes had completed meiosis I or II [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Intrafollicular estrogen is thought to be involved in modulation of the maturation process of bovine oocytes [15]. Exposure of oocytes to abnormally high concentrations of estrogen over extended periods of time could lead to abnormal development of oocytes in bovine females treated with norgestomet.…”
Section: Discussionmentioning
confidence: 99%